SISTEM MITIGASI LONGSOR BERBASIS INTERNET OF THINGS (IoT) PADA KELOMPOK SI BEJO DI KELURAHAN KALIREJO, KULON PROGO: SISTEM MITIGASI LONGSOR BERBASIS INTERNET OF THINGS (IoT) PADA KELOMPOK SI BEJO DI KELURAHAN KALIREJO, KULON PROGO - Yuli Fajarwati; Elviana; Oktaf Agni Dhewa (Politeknik Negeri Semarang, 2026)
Kalirejo Village, Kokap Subdistrict, Kulon Progo Regency, is one of the areas with a high level of vulnerability to landslides due to the geological conditions and hilly topography as well as high rainfall. The lack of vulnerability zoning maps and evacuation routes makes it difficult for the community to take quick and appropriate mitigation measures. This Community Service Program (PkM) aims to develop a landslide mitigation system based on Internet of Things (IoT) technology through the Sibejo Rescue application and by installing evacuation signs at strategic points. The implementation method includes a field survey to identify locations prone to landslides, soil characteristic testing, vulnerability mapping using a Geographic Information System (GIS), designing the IoT-based Sibejo Rescue application, testing the application with village officials, and installing evacuation route signs and assembly points. The results of the activity showed that the landslide vulnerability map was successfully compiled into three categories (low, medium, high) and integrated into the Sibejo Rescue application. Limited trials with village officials showed that the application can display spatial information in the form of vulnerability maps, evacuation routes, and shelter points functionally. In addition, the installed evacuation signs facilitate the identification of Rescue routes when a disaster occurs. The conclusion of this activity is that the integration of vulnerability maps, IoT applications, and evacuation signs can be a first step towards improving landslide mitigation in Kalirejo, although broader public awareness campaigns are still needed in the next phase